Me, myself, and I: self-referent word use as an indicator of self-focused attention in relation to depression and anxiety - Brockmeyer, Timo; Zimmermann, Johannes; Kulessa, Dominika; Hautzinger, Martin; Bents, Hinrich; Friederich, Hans-Christoph; Herzog, Wolfgang; Backenstrass, Matthias (Frontiers in Psychology, 2015)
Self-focused attention (SFA) is considered a cognitive bias that is closely related to depression. However, it is not yet well understood whether it represents a disorder-specific or a trans-diagnostic phenomenon and which role the valence of a given context is playing in this regard. Computerized quantitative text-analysis offers an integrative psycho-linguistic approach that may help to provide new insights into these complex relationships. The relative frequency of first-person singular pronouns in natural language is regarded as an objective, linguistic marker of SFA. Here we present two studies that examined the associations between SFA and symptoms of depression and anxiety in two different contexts (positive vs. negative valence), as well as the convergence between pronoun-use and self-reported aspects of SFA. In the first study, we found that the use of first-person singular pronouns during negative but not during positive memory recall was positively related to symptoms of depression and anxiety in patients with anorexia nervosa with varying levels of co-morbid depression and anxiety. In the second study, we found the same pattern of results in non-depressed individuals. In addition, use of first-person singular pronouns during negative memory recall was positively related to brooding (i.e. the assumed maladaptive sub-component of rumination) but not to reflection. These findings could not be replicated in two samples of depressed patients. However, non-chronically depressed patients used more first-person singular pronouns than healthy controls, irrespective of context. Taken together, the findings lend partial support to theoretical models that emphasize the effects of context on self-focus and consider SFA as a relevant trans-diagnostic phenomenon. In addition, the present findings point to the construct validity of pronoun-use as a linguistic marker of maladaptive self-focus.